Analysis of novel PBI/ZrP hybrid membrane-based CuCl-HCl electrolytic system on the performance of hydrogen production by FFD and RSM - Ahmad Kamaroddin, Mohd Fadhzir; Sabli, Nordin; Tuan Abdullah, Tuan Amran; Abdullah, Luqman Chuah; Izhar, Shamsul; Hassan, Nurul Sahida; Abdul Jalil, Aishah (Tamkang University, 2025)
Currently, the Copper Chloride (CuCl) hydrogen electrolytic process is integrated into the CuCl thermochemical cycle, operating at low temperatures and relying on expensive Nafion and Nafionbased membranes. This study demonstrates significant innovation by introducing a polybenzimidazole/ zirconium phosphate (PBI/ZrP) hybrid membrane, which exhibits a four-fold increase in proton conductivity compared to pristine polybezimidazole (PBI), addressing the limitations of conventional Nafion membranes in high-temperature hydrogen production. In this research, we investigate a high-temperature CuCl hydrogen electrolytic process that utilizes a hybrid membrane as an alternative to Nafion for hydrogen production. For the optimization study, a pre-synthesized PBI/ZrP hybrid membrane was used, where its proton conductivity shows a four-fold increase compared to pristine PBI. Response surface methodology (RSM) with a central composite design (CCD) was employed. The optimized parameters-116°C temperature, 0.773 A cm−2 current density, and 0.075 M CuCl concentration-yielded an optimal hydrogen production rate of 0.7167 cm3 min−1The actual hydrogen yield from these parameters reached 0.7709 cm3 min−1, with only a 7.56% discrepancy from the predicted value. In conclusion, this study showcases the efficacy of the high-temperature CuCl hydrogen electrolytic process using a PBI/ZrP hybrid membrane as a superior alternative to Nafion. This process not only maximizes hydrogen output but also optimizes operating parameters, thereby reducing associated hydrogen production costs.